Raman spectroscopy a promising technique for investigations of metallothioneins. - Torreggiani, Armida; Tinti, Anna (Metallomics : integrated biometal science, 2010)
Metallobiomolecules are highly elaborated coordination complexes, and their fundamental metal-ligand interactions are critical components of metalloprotein folding, assembly, stability, electrochemistry, and catalytic function. Herein, we have described the benefits in using Raman spectroscopy to define the metal-ion binding properties of MTs toward metal ions such as Zn(ii) and Cd(ii). In particular, this vibrational technique can shed light on the secondary structures eventually present in MTs and the ligands involved in metal coordination. The oxidation state of Cys residues and their participation in the metal chelation can be clearly defined, as well as the eventual involvement of His residues. With regards to exogenous metal ligands such as sulfide anions, their presence can be identified by some marker bands whose intensity is linearly correlated with sulfide/metal molar ratio. Finally, Raman can be also an useful tool for providing information on the favourite sites of the radical attack and radical-induced modification in protein folding. In conclusion, many advantages such as the capability of defining local regions in large complexes and detecting several structural features at the same time, the ability in supporting mechanisms, as well as the requirement of low sample amount, make to propose Raman spectroscopy, in coupling with analytical techniques such as atomic emission spectroscopy, gas chromatography, and circular dichroism, as one of the most promising experimental strategies in the research on structure-activity relationships in MTs.
Keywords: copper; Copper: chemistry; Copper: metabolism; metallothionein; Metallothionein: chemistry; Metallothionein: metabolism; Spectrum Analysis, Raman; Spectrum Analysis, Raman: methods; Structure-Activity Relationship; Zinc; Zinc: chemistry; Zinc: metabolism

Leaf accumulation of trace elements and polycyclic aromatic hydrocarbons (PAHs) in Quercus ilex L. - De Nicola, F; Maisto, G; Prati, M V; Alfani, a (Environmental pollution (Barking, Essex : 1987), 2008)
Quercus ilex L. leaves were collected four times in one year at six urban sites and one remote area in order to determine trace element and PAH accumulation through concomitant analyses of unwashed and water-washed leaves. Both unwashed and washed leaves showed the highest amounts of trace elements and PAHs in the urban area. Unwashed leaves showed greater differences between urban and remote areas and among the urban sites than washed leaves for trace element and PAH concentrations. Water-washing resulted in a significant (P<0.001) decrease in leaf concentrations of Cr, Cu, Fe, Pb, V and Zn. By contrast, Cd and total PAH concentrations showed no differences between unwashed and washed leaves.
Keywords: Air Pollutants; Air Pollutants: analysis; Aromatic; Aromatic: analysis; Atomic; biomonitoring; cadmium; Cadmium: analysis; chromium; Chromium: analysis; Cities; copper; Copper: analysis; Environmental Monitoring; Environmental Monitoring: methods; Iron; Iron: analysis; Italy; lead; Lead: analysis; PAHs; Plant Leaves; Plant Leaves: chemistry; Polycyclic Hydrocarbons; Quercus; Quercus ilex L.; Spectrophotometry; Trace Elements; Trace Elements: analysis; Unwashed and washed leaves; Vanadium; Vanadium: analysis; Zinc; Zinc: analysis

Leaf accumulation of trace elements and polycyclic aromatic hydrocarbons (PAHs) in Quercus ilex L. - De Nicola, F.; Maisto, G.; Prati, M. V.; Alfani, A. (Environmental pollution (Barking, Essex : 1987), 2008)
Quercus ilex L. leaves were collected four times in one year at six urban sites and one remote area in order to determine trace element and PAH accumulation through concomitant analyses of unwashed and water-washed leaves. Both unwashed and washed leaves showed the highest amounts of trace elements and PAHs in the urban area. Unwashed leaves showed greater differences between urban and remote areas and among the urban sites than washed leaves for trace element and PAH concentrations. Water-washing resulted in a significant (P<0.001) decrease in leaf concentrations of Cr, Cu, Fe, Pb, V and Zn. By contrast, Cd and total PAH concentrations showed no differences between unwashed and washed leaves.
The following values have no corresponding Zotero field: accession-num: 17892907
Keywords: Air Pollutants; Air Pollutants: analysis; Aromatic; Aromatic: analysis; Atomic; biomonitoring; cadmium; Cadmium: analysis; chromium; Chromium: analysis; Cities; copper; Copper: analysis; Environmental Monitoring; Environmental Monitoring: methods; Iron; Iron: analysis; Italy; lead; Lead: analysis; PAHs; Plant Leaves; Plant Leaves: chemistry; Polycyclic Hydrocarbons; Quercus; Quercus ilex L.; Spectrophotometry; Trace Elements; Trace Elements: analysis; Unwashed and washed leaves; Vanadium; Vanadium: analysis; Zinc; Zinc: analysis

Copper(II) and nickel(II) uptake from aqueous solutions by cork wastes: a NMR and potentiometric study - Villaescusa, Isabel; Fiol, Núria; Cristiani, Franco; Floris, Costantino; Lai, Simona; Nurchi, Valeria Marina (Polyhedron, 2002)
Due to the increasing interest in the use of biomasses from agriculture as removing agents for heavy metals in waste effluents, we present here a joint potentiometric and 13C MAS and cross polarization-magic angle spinning NMR (CP-MAS NMR) study on cork interaction with Cu(II) and Ni(II). Through potentiometry we were able to distinguish two kind of interactions, a stronger one which involves protonated sites on cork and a second that allows hydroxide precipitation of the bound metal ion into the cork structure. NMR signal analysis suggests a specific metal complexation on the carbohydrate moieties of polymeric cork matrix. The 13C MAS NMR suggests that the dynamics in the MHz range and the overall arrangement of polymeric matrix is not affected by metal binding; and the spin relaxation times T1ρ(1H) and T1ρ(13C) show that no significant difference of relaxation processes in the KHz range is introduced by metal coordination.
Keywords: copper; Cork; Metal uptake; Nickel; Potentiometric titration; Solid state 13C MAS and CP-MAS NMR

Copper(II) and nickel(II) uptake from aqueous solutions by cork wastes: a NMR and potentiometric study - Villaescusa, Isabel; Fiol, Núria; Cristiani, Franco; Floris, Costantino; Lai, Simona; Nurchi, Valeria Marina (Polyhedron, 2002)
Due to the increasing interest in the use of biomasses from agriculture as removing agents for heavy metals in waste effluents, we present here a joint potentiometric and 13C MAS and cross polarization-magic angle spinning NMR (CP-MAS NMR) study on cork interaction with Cu(II) and Ni(II). Through potentiometry we were able to distinguish two kind of interactions, a stronger one which involves protonated sites on cork and a second that allows hydroxide precipitation of the bound metal ion into the cork structure. NMR signal analysis suggests a specific metal complexation on the carbohydrate moieties of polymeric cork matrix. The 13C MAS NMR suggests that the dynamics in the MHz range and the overall arrangement of polymeric matrix is not affected by metal binding; and the spin relaxation times T1ρ(1H) and T1ρ(13C) show that no significant difference of relaxation processes in the KHz range is introduced by metal coordination.
Keywords: copper; Cork; Metal uptake; Nickel; Potentiometric titration; Solid state 13C MAS and CP-MAS NMR

Susceptibility of hepatic tissue of Iberian pigs is enhanced by free-range feeding and reduced by vitamin E supplementation - López Bote, C. J.; Rey, A. I. (Nutrition Research, 2001)
The effect of feeding system (free-range vs conﬁnement) and the supplementation of concentrated feed with vitamin E and copper was investigated. Dietary copper supplementation (100 mg/kg) increased the hepatic concentration of copper in hepatic tissue (P , 0.05), reaching similar concentrations than pigs fed under free-range conditions. Free-range feeding produced higher concentration of a-tocopherol than those from pigs fed in conﬁnement with the basal level of vitamin E, but lower values than pigs fed supplemented levels, which may be attributed to the relative high concentration of a-tocopherol in the grass. Liver samples from pigs under free-range conditions showed higher susceptibility to lipid oxidation than pigs produced in conﬁnement and fed mixed diets. No signiﬁcant effect of copper was observed in hepatic tissue oxidation, but vitamin E supplementation markedly decreased oxidation
Keywords: a-tocopherol; copper; fatty acid; liver; pig

Removal of toxic metals from solution by leaf, stem and root phytomass of Quercus ilex L. (holly oak). - Prasad, M. N.; Freitas, H. (Environmental pollution (Barking, Essex : 1987), 2000)
Increased consciousness for safeguarding the aqueous environment has prompted a search for alternative technologies for the removal of toxic metal ions from aqueous solutions. In this regard, a wide variety of biomass is being considered as adsorbents of heavy metals for treatment of industrial and domestic wastewaters as well as natural waters, including drinking water. In the present investigation, the potential of Quercus ilex phytomass from stem, leaf and root as an adsorbent of chromium (Cr), nickel (Ni), copper (Cu), cadmium (Cd) and lead (Pb) at ambient temperature was investigated. The metal uptake capacity of the root for different metals was found to be in the order: Ni>Cd>Pb>Cu>Cr; stem Ni>Pb>Cu>Cd>Cr; and leaf Ni>Cd>Cu>Pb>Cr. The highest amount adsorbed was Ni (root>leaf>stem). Data from this laboratory demonstrated that Ni is sequestered mostly in the roots, where concentrations can be as high as 428.4 ng/g dry wt., when 1-year-old seedlings were treated with Ni (2000 mg/l) in pot culture experiments, compared to 7.63 ng/g dry wt., control (garden and greenhouse soil) topsoil where Ni was present in trace amounts. This proves that the root biomass of Q. ilex has the capacity for complexing Ni. Cr exhibited the least adsorption values for all the three types of phytomass compared to other metals. The trend of adsorption of the phytomass was similar for Ni and Cd, i.e. root>leaf>stem. Desorption with 10 mM Na(4) EDTA was effective (55-90%) and, hence, there exists the possibility of recycling the phytomass. The biosorption results of recycled phytomass suggest that the selected adsorbents are re-usable. The advantages and potential of the Q. ilex phytomass as a biofilter of toxic trace metals, the scope and need for enhancing the efficiency of the Q. ilex phytomass as an adsorbent of metals are presented.
The following values have no corresponding Zotero field: accession-num: 15092842
Keywords: Biosorption; cadmium; chromium; copper; desorption; lead; Nickel; phytomass; Quercus ilex; root; stem

Removal of toxic metals from solution by leaf, stem and root phytomass of Quercus ilex L. (holly oak). - Prasad, M N; Freitas, H (Environmental pollution (Barking, Essex : 1987), 2000)
Increased consciousness for safeguarding the aqueous environment has prompted a search for alternative technologies for the removal of toxic metal ions from aqueous solutions. In this regard, a wide variety of biomass is being considered as adsorbents of heavy metals for treatment of industrial and domestic wastewaters as well as natural waters, including drinking water. In the present investigation, the potential of Quercus ilex phytomass from stem, leaf and root as an adsorbent of chromium (Cr), nickel (Ni), copper (Cu), cadmium (Cd) and lead (Pb) at ambient temperature was investigated. The metal uptake capacity of the root for different metals was found to be in the order: Ni>Cd>Pb>Cu>Cr; stem Ni>Pb>Cu>Cd>Cr; and leaf Ni>Cd>Cu>Pb>Cr. The highest amount adsorbed was Ni (root>leaf>stem). Data from this laboratory demonstrated that Ni is sequestered mostly in the roots, where concentrations can be as high as 428.4 ng/g dry wt., when 1-year-old seedlings were treated with Ni (2000 mg/l) in pot culture experiments, compared to 7.63 ng/g dry wt., control (garden and greenhouse soil) topsoil where Ni was present in trace amounts. This proves that the root biomass of Q. ilex has the capacity for complexing Ni. Cr exhibited the least adsorption values for all the three types of phytomass compared to other metals. The trend of adsorption of the phytomass was similar for Ni and Cd, i.e. root>leaf>stem. Desorption with 10 mM Na(4) EDTA was effective (55-90%) and, hence, there exists the possibility of recycling the phytomass. The biosorption results of recycled phytomass suggest that the selected adsorbents are re-usable. The advantages and potential of the Q. ilex phytomass as a biofilter of toxic trace metals, the scope and need for enhancing the efficiency of the Q. ilex phytomass as an adsorbent of metals are presented.
Keywords: Biosorption; cadmium; chromium; copper; desorption; lead; Nickel; phytomass; Quercus ilex; root; stem

Trace metal biomonitoring in the soil and the leaves of Quercus ilex in the urban area of Naples. - Alfani, a; Bartoli, G; Rutigliano, F a; Maisto, G; De Santo, a V (Biological trace element research, 1996)
The concentrations of Pb, Cu, Fe, and Mn were analyzed in surface deposit and tissue of Quercus ilex leaves from several sites of the urban area of Naples, exposed to different degrees of air pollution. These included some major roads with heavy traffic loads, squares, and three urban parks. The soil from the trunk base area of Q. ilex trees in the same sites was also analyzed for total and available metal contents. Pb, Cu, and Fe contents in the surface deposit and leaf tissue were significantly higher (p < 0.01) in leaves from roadside sites than in leaves from parks; significant correlations were found between deposit- and tissue-contents of Pb, Cu, and Fe. Mn content in leaves from roadside sites and in leaves from parks were similar and Mn content in the leaf deposit was irrelevant. Significant differences (p < 0.001) in both total and available Pb and Cu soil content were found between sampling sites. Also for available Fe and Mn soil content differences among sites were relevant, although the highest values were measured in soil from urban parks. A positive correlation between leaf and soil metal content was found only for Pb, thus suggesting that trace metal contents of leaves directly depend on atmospheric depositions. Seasonal variations of Pb, Cu, and Fe were pronounced at a polluted site, whereas no relevant seasonal variation was observed at a control site; moreover, metal accumulation was high at the polluted site. Mn content and seasonal dynamics were comparable at control and polluted sites.
Keywords: Air Pollutants; Air Pollutants: analysis; biomonitoring; copper; Copper: analysis; Environmental Monitoring; Holly Oak; Iron; Iron: analysis; lead; Lead: analysis; leaves; Manganese; Manganese: analysis; Plants; Plants: chemistry; seasonal dynamics; Soil; Soil: analysis; Trace Elements; Trace Elements: analysis; urban area pollution

Trace metal biomonitoring in the soil and the leaves of Quercus ilex in the urban area of Naples. - Alfani, a; Bartoli, G.; Rutigliano, F. a; Maisto, G.; De Santo, a V. (Biological trace element research, 1996)
The concentrations of Pb, Cu, Fe, and Mn were analyzed in surface deposit and tissue of Quercus ilex leaves from several sites of the urban area of Naples, exposed to different degrees of air pollution. These included some major roads with heavy traffic loads, squares, and three urban parks. The soil from the trunk base area of Q. ilex trees in the same sites was also analyzed for total and available metal contents. Pb, Cu, and Fe contents in the surface deposit and leaf tissue were significantly higher (p < 0.01) in leaves from roadside sites than in leaves from parks; significant correlations were found between deposit- and tissue-contents of Pb, Cu, and Fe. Mn content in leaves from roadside sites and in leaves from parks were similar and Mn content in the leaf deposit was irrelevant. Significant differences (p < 0.001) in both total and available Pb and Cu soil content were found between sampling sites. Also for available Fe and Mn soil content differences among sites were relevant, although the highest values were measured in soil from urban parks. A positive correlation between leaf and soil metal content was found only for Pb, thus suggesting that trace metal contents of leaves directly depend on atmospheric depositions. Seasonal variations of Pb, Cu, and Fe were pronounced at a polluted site, whereas no relevant seasonal variation was observed at a control site; moreover, metal accumulation was high at the polluted site. Mn content and seasonal dynamics were comparable at control and polluted sites.
The following values have no corresponding Zotero field: accession-num: 8834387
Keywords: Air Pollutants; Air Pollutants: analysis; biomonitoring; copper; Copper: analysis; Environmental Monitoring; Holly Oak; Iron; Iron: analysis; lead; Lead: analysis; leaves; Manganese; Manganese: analysis; Plants; Plants: chemistry; seasonal dynamics; Soil; Soil: analysis; Trace Elements; Trace Elements: analysis; urban area pollution